Cost accounting : a managerial emphasis - Horngren, Charles T.; Foster, George (New Delhi, Indian : Pearson Prentice Hall, 1988)
This book defines how cost accounting market had continued to innovate in today market by consistently integrating the most current practice and theory. This acclaimed, number one market-leading book embraces the basic theme of "different costs for different purposes." It reaches beyond cost accounting procedures to consider concepts, analyses, and management. This latest edition of "Cost Accounting "incorporates the latest research and most up-to-date thinking into all relevant chapters. Professional issues related to Management Accounting and Management Accountants are emphasized
Includes bibliographical references (p. 829-831) and indexes.
jbi, 20/03/2018
Loans
Keywords: Cost accounting; Costs, Industrial; Managerial accounting